Assessment and modification of buoyancy criteria for supercritical pressure CO2 convection heat transfer in a horizontal tube. (25th March 2020) - Zhao, Zhehua; Yuan, Baoqiang; Du, Wenjing
Highlights: Ten turbulence models are validated and the most accurate one is recommend. Cases with and without gravity are calculated to assess the buoyancy effects. The onset of buoyancy effect on overall heat transfer performance is captured. Three buoyancy criteria are estimated and the novel thresholds are proposed. Abstract: Buoyancy has significant effects on convection heat transfer of supercritical pressure fluids. This paper numerically investigates the asymmetric heat transfer characteristics of supercritical pressure CO2 in a horizontal tube with taking buoyancy effects into account. The applicability of three buoyancy criteria is validated by the computational results and new thresholds for buoyancy parameters are proposed. The software ANSYS FLUENT is adopted for present work. The computational variable is heat flux ranging from 1 kW/m 2 to 22 kW/m 2, the computational constants include tube diameter (22.14 mm), inlet temperature (288.55 K), outlet pressure (7.59 MPa) and mass flow rate (0.148 kg/s). The outlet temperatures for all cases are less than the pseudo-critical temperature. Results show that the asymmetric heat transfer does not change with the magnitude of buoyancy and the variation of overall heat transfer performance desynchronizes with the appearance of natural convection. The original thresholds of two buoyancy parameters are small to indicate the onset of buoyancy effect on overall heat transfer performance, the recommended critical values are given in this paper. The other buoyancy parameter is unsuitable to predict the buoyancy effect on overall heat transfer performance.